2022
DOI: 10.1111/jpc.16197
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus, recurrent wheeze and asthma: A narrative review of pathophysiology, prevention and future directions

Abstract: Globally, respiratory syncytial virus (RSV) is the leading cause of bronchiolitis and pneumonia in young children, and the association between severe RSV disease and later recurrent wheeze and asthma is well established. Whilst a causal link between RSV and wheeze/asthma is not yet proven, immunological evidence suggests skewing towards a Th2‐type response, and dampening of IFN‐γ antiviral immunity during RSV infection underpins airway hyper‐reactivity in a subset of susceptible children after RSV infection. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
0
15
0
2
Order By: Relevance
“…The measures to control the transmission of infections were: the use of masks, social distancing, working from home, limiting gatherings, and increasing hygiene measures. These interventions, which were aimed at limiting the transmission of SARS-Cov-2, also had an important impact on other airborne viruses, such as influenza viruses, measles, rubella [35], respiratory syncytial virus, common human coronaviruses (HCoVs), parainfluenza viruses, and metapneumoviruses [36,37]. However, since most laboratories were busy battling the scourge of SARS-CoV-2, it is likely that the decrease in circulation was also compounded by the underdiagnosis of other airborne viruses [36].…”
Section: Discussionmentioning
confidence: 99%
“…The measures to control the transmission of infections were: the use of masks, social distancing, working from home, limiting gatherings, and increasing hygiene measures. These interventions, which were aimed at limiting the transmission of SARS-Cov-2, also had an important impact on other airborne viruses, such as influenza viruses, measles, rubella [35], respiratory syncytial virus, common human coronaviruses (HCoVs), parainfluenza viruses, and metapneumoviruses [36,37]. However, since most laboratories were busy battling the scourge of SARS-CoV-2, it is likely that the decrease in circulation was also compounded by the underdiagnosis of other airborne viruses [36].…”
Section: Discussionmentioning
confidence: 99%
“… Targeting inflammatory molecules/anti-inflammatory molecules Danirixin (GSK1325756) RV568, (narrow spectrum kinase inhibitor) [ 20 , 21 , 27 , 50 , 51 , 54 , 58 , 79 ], 7. Prophylactics and immunoregulators MEDI 557 (recombinant human monoclonal antibody) MEDI 8897 (human RSV monoclonal antibody) RI-001 (polyclonal antibody) Motavizumab (MEDI-524), derived from palivizumab Trivalent nanobody ALX-0171 D25 RSV antibody (against F glycoproteins) (RSV-IVIG, RespiGam) intravenous immunoglobulin Palivizumab (humanized monoclonal IgG1 antibody) ALX-0171 (a nanobody preparation) REGN2222, (human monoclonal IgG1 antibody against RSV-F) MEDI-557 (derived from motavizumab) MEDI-8897, derived from D25-, an anti-RSV F MAb) [ 106 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ] …”
Section: Main Bodymentioning
confidence: 99%
“…18 We observed that children singly positive for RSV had significantly increased odds of receiving a breathing treatment and antibiotics even after controlling for age and comorbidities, which is unsurprising given the known pathogenesis and virulence of RSV in children. [27][28][29] Although no difference was observed between hospitalizations between patients with HRV/ENT and RSV, children singly positive for RSV had nearly 85% decreased odds of PICU admission than those with HRV/ENT after controlling for age and comorbid conditions. Future studies with larger numbers of PICU admissions across viruses are needed to evaluate the validity of this finding.…”
Section: Hrv/ent Compared To Rsvmentioning
confidence: 99%